The device-aided intrajejunal delivery of levodopa–entacapone–carbidopa intestinal gel the treatment of Parkinson’s disease: overview of efficacy and safety - Popławska-Domaszewicz, Karolina; Metta, Vinod; Odin, Per; Chaudhuri, K Ray (Expert review of medical devices, 2025)
Device-aided therapies (DATs) have been developed to provide continuous drug delivery (CDD) to people with advanced Parkinson's disease (PD) whose symptoms can no longer be effectively managed with oral or transdermal therapy. Intrajejunal infusion of levodopa-carbidopa intestinal gel (LCIG), delivered via the CADD Legacy 1400 pump, is an established CDD option, while levodopa-entacapone-carbidopa intestinal gel (LECIG), delivered via the Crono LECIG pump, is a more recent addition to the range of DAT options in Europe. This article explores the rationale for the development of LECIG infusion, the role of entacapone in the formulation, and the attributes and specifications of the LECIG infusion pump device. Clinical and real-world data reporting its efficacy, safety and tolerability of LECIG in advanced PD patients from a range of European centers are reviewed, with a focus on the practical benefits that a smaller, lighter and quieter device can provide for patients who wish to start treatment with intrajejunal levodopa infusion. LECIG infusion delivered via the LECIG infusion pump offers another valuable DAT option to consider for suitable people with advanced PD providing both good long-term clinical benefits and a favorable treatment experience for patients.